Body image dissatisfaction among medical students in the Southern district of Kerala: a cross-sectional study - Siraj, Mehna; B. Palappillil, Merin; Varghese, Merin; Manivarnan, Megha; Saiji Alexander, Merlin; Varghese, Betsy; Prajitha, K. C. (International Journal Of Community Medicine And Public Health, 2022)
Background: Body image misconception can lead to behaviors that are detrimental to mental as well as physical health. Body dissatisfaction develops when people have negative thoughts about their body image. In this context, estimating the prevalence of body dissatisfaction would help in providing valuable information about those at risk of developing eating and other psychiatric disorders. Methods: A cross-sectional study was conducted among undergraduate students studying in a tertiary care government health institution in the southern district of Kerala. Data was collected using an online semi-structured questionnaire and was administered to 200 eligible participants. Data was analyzed using IBM SPSS statistics for windows (version 25.0. Armonk, NY) Results: Among the 200 participants in the study, 36 (18%) were found to have body image concerns without any significant gender predilection. Dissatisfaction with body image was seen to be more prevalent in those with higher BMI. There was a positive association between body image dissatisfaction and socio-cultural pressure to change body fat levels (p=0.001). It was also found that the tendency to skip meals was more among those with higher body image concerns (p=0.001). Conclusions: The study concluded that about one-fifth of the study participants comprising medical students have moderate to severe body image dissatisfaction without significant gender predilection. Dissatisfaction with body image was seen to be more prevalent in those with higher BMI. The focus should be on initiating educational programs to promote positive body image, and acceptance of self and individual differences while maintaining optimum weight and active lifestyle.